Canción abierta: contrapuntos en Santa Bárbara - Campos Pariasca, Claudia Sofía (2024)
The project takes as its starting point a cultural manifestation of which no records are preserved: the jaranas in the colonial sugar plantation Santa Bárbara located in San Luis de Cañete. Thinking of a jarana in a sugar plantation has an ethnic, historical and cultural charge if we look at the history of sugar in relation to slavery, as well as afroperuvian musical expression as a response to a stripped-down origin. In this work the musical counterpoint is extrapolated to other aspects present in the meeting of people in a jarana such as ethnic, discursive, spatial, among others. Drawing on Cañete’s public music archives, such as recordings or interviews, and generating new sounds allows me to create a space of other forms of narration, listening and encounter, where music, dialogue, bodies and history coexist. The proposal is to resume what could be a jarana in the aforementioned sugar plantation house. But the jarana, a cultural manifestation that belongs to the past of that hacienda today in ruins, can continue to be effective in a present that seeks to be confronted, or counterpointed by those who give it life today. To what extent are we aware of the historical burdens that stain our sounds and music? Could the moment of the jarana be a possibility of temporary harmony for a society that fails to put an end to discriminatory violence?